The pruritogenic mediator endothelin‐1 shifts the dendritic cell–T‐cell response toward Th17/Th1 polarization. Issue 2 (11th October 2017) - Nakahara, T.; Kido‐Nakahara, M.; Ohno, F.; Ulzii, D.; Chiba, T.; Tsuji, G.; Furue, M.
Abstract: Endothelin‐1 (ET‐1) is associated with skin diseases such as atopic dermatitis (AD) and psoriasis. ET‐1 is enhanced in the skin of patients AD and psoriasis. In addition, plasma levels of ET‐1 are elevated in AD and psoriasis. Although both AD and psoriasis are T‐cell–mediated skin diseases, the association between ET‐1 and the T‐cell immune response has not been clarified. To evaluate the role of ET‐1 in inflammatory skin disease, we sought to investigate the effects of ET‐1 on the functions of dendritic cells (DCs) and subsequent immune responses. For this purpose, we immunohistochemically confirmed the upregulation of ET‐1 in the epidermis of patients with AD or psoriasis. ET‐1 directly induced phenotypic maturation of bone marrow‐derived DCs (BMDCs). In addition, ET‐1 augmented the production of several cytokines and allogeneic stimulatory capacity of BMDCs. Interestingly, ET‐1–activated BMDCs primed T cells to produce Th1 and Th17 cytokines, but not Th2 cytokines. These findings indicate that ET‐1 polarizes the DC–T‐cell response toward Th17/1 differentiation and may augment the persistent course of inflammatory skin diseases.